Odpowiedzi

2009-11-25T21:39:04+01:00
{6x+5y=1+3x+y
{3x+7y=2x+0,5+4y

{3x+4y=1
{x+3y=0,5 /*(-3)

{3x+4y=1
+{-3x-9y=-1,5

-5y=-0,5 /:5

y=0,1


{y=0,1
{x+3*0,1=05

{y=0,1
{x=0,2
2009-11-25T21:43:02+01:00
6x + 5y = 1 + 3x + y
3x + 7y = 2x + 0,5 + 4y

3x + 4y = 1
x + 3y = 0,5

3x + 4y = 1
-3x - 9y = -1,5

-5y = -0,5
y = 0,1

y = 0,1
3x + 4 * 0,1 = 1

y = 0,1
x = 0,2
2009-11-25T21:44:50+01:00
6x + 5y = 1 +3x + y
3x + 7y = 2x + 0,5 + 4y

3x + 4y = 1 | *3
x + 3y = 0,5 | * (-4)

9x + 12y = 1
-4x - 12 y = -2

5x = -1
x = 1/5